Penggunaan Aplikasi Wordwall Sebagai Alat Evaluasi Pembelajaran Di SD Negeri 2 Jabung - Dina Celline; Yulia Ruti Cahyanti; Isna Rahmawati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The role of technology today has a big influence on education. Technology can be utilized by teachers and students in the teaching and learning process. One technology that can be used is learning media, one of which is the Wordwall game. This research aims to provide a description and study regarding the use of the Wordwall game application in learning to foster students' interest in learning in elementary schools. In this research, researchers used qualitative research and used descriptive analysis techniques. The results of this research show that the use of wordwall as an evaluation tool at SDN 2 Jabung in class IV science subjects is able to attract students' interest and attention.